Difference between revisions of "2005 AIME II Problems/Problem 7"

(Problem)
(Solution)
Line 3: Line 3:
  
 
== Solution ==
 
== Solution ==
 +
The expression for <math>x</math> looks very suspicious.  We multiply top and bottom by <math>(\sqrt[16]{5} -1)</math>.
 +
 +
<math>(\sqrt{5}+1)(\sqrt[4]{5}+1)(\sqrt[8]{5}+1)(\sqrt[16]{5}+1)(\sqrt[16]{5} -1) = (\sqrt{5}+1)(\sqrt[4]{5}+1)(\sqrt[8]{5}+1)((\sqrt[16]{5})^2 - 1) = (\sqrt{5}+1)(\sqrt[4]{5}+1)(\sqrt[8]{5}+1)(\sqrt[8]{5} - 1) = </math>
 +
<math>= (\sqrt{5}+1)(\sqrt[4]{5}+1)((\sqrt[8]{5})^2-1) = (\sqrt{5}+1)(\sqrt[4]{5}+1)(\sqrt[4]{5}-1) = (\sqrt{5}+1)((\sqrt[4]{5})^2-1) = (\sqrt5 + 1)(\sqrt5 - 1) = 4</math>.
 +
(This is an example of a [[telescoping]] expression.  An alternative way to recognize the telescoping nature would be to write roots as [[fractional exponent]]s, to write everything in terms of <math>\sqrt[16]5</math>, or to expand the denominator out entirely.)
 +
 +
Thus, we have immediately that <math>x= \frac{4(\sqrt[16]5 - 1)}{4} = \sqrt[16]5 - 1</math> so <math>(x + 1)^{48} = (\sqrt[16]5)^{48} = 5^3 = 125</math>
 
== See Also ==
 
== See Also ==
 
*[[2005 AIME II Problems]]
 
*[[2005 AIME II Problems]]

Revision as of 09:12, 21 July 2006

Problem

Let $x=\frac{4}{(\sqrt{5}+1)(\sqrt[4]{5}+1)(\sqrt[8]{5}+1)(\sqrt[16]{5}+1)}.$ Find $(x+1)^{48}.$

Solution

The expression for $x$ looks very suspicious. We multiply top and bottom by $(\sqrt[16]{5} -1)$.

$(\sqrt{5}+1)(\sqrt[4]{5}+1)(\sqrt[8]{5}+1)(\sqrt[16]{5}+1)(\sqrt[16]{5} -1) = (\sqrt{5}+1)(\sqrt[4]{5}+1)(\sqrt[8]{5}+1)((\sqrt[16]{5})^2 - 1) = (\sqrt{5}+1)(\sqrt[4]{5}+1)(\sqrt[8]{5}+1)(\sqrt[8]{5} - 1) =$ $= (\sqrt{5}+1)(\sqrt[4]{5}+1)((\sqrt[8]{5})^2-1) = (\sqrt{5}+1)(\sqrt[4]{5}+1)(\sqrt[4]{5}-1) = (\sqrt{5}+1)((\sqrt[4]{5})^2-1) = (\sqrt5 + 1)(\sqrt5 - 1) = 4$. (This is an example of a telescoping expression. An alternative way to recognize the telescoping nature would be to write roots as fractional exponents, to write everything in terms of $\sqrt[16]5$, or to expand the denominator out entirely.)

Thus, we have immediately that $x= \frac{4(\sqrt[16]5 - 1)}{4} = \sqrt[16]5 - 1$ so $(x + 1)^{48} = (\sqrt[16]5)^{48} = 5^3 = 125$

See Also

Invalid username
Login to AoPS